O fim do financiamento de pessoas jurídicas em campanhas eleitorais: uma análise da competição eleitoral utilizando índice de GINI nas eleições de 2014 e 2018 - Cavalcante, Carlos Fabiano Pinheiro (2020)
The Brazilian electoral system has undergone changes over time, in order to keep it current and improved. One of the most recent changes concerns the financing of an electoral campaign, guided by the Direct Action of Unconstitutionality (ADI) 4.650 / DF, judged on September 17, 2015, which declares the financing of electoral campaigns by legal entities prohibited. With the objective of judging whether this Action had a positive impact on the elections, this paper seeks to make a comparative analysis of the elections for the position of Federal Deputy of 2014 - last election before the ADI 4.650 / DF - and 2018, the first election after the Action. The impact of the measure will be assessed in the form of electoral competition, through the Gini Index, which will measure the concentration of votes ranging from 0 to 1, thus, indexes closer to 1 indicate a greater concentration of votes in a few candidates, while those closer to 0 indicate a greater distribution of votes in more candidates, which represents a more competitive scenario. The Gini indices of the 26 states and the Federal District were calculated for the two years in question, using data from the Superior Electoral Court (TSE) of the number of votes of all candidates, and it was observed that despite a decrease in the Gini Index , the statistical test showed that this reduction was not significant, leading to the conclusion that there are more factors to be considered to explain this improvement in competition, such as the greater dynamism that social networks brought to the campaigns, enabling successful applications at a low cost.